A comparison of four decontamination procedures in Reusing healing abutments: An in vitro study - Narges Naghsh; Arezoo Hosseini; Ahmad Mogharehabed; Jaber Yaghini; Zahra Pezeshki; Niloofar Khaleghi (Elsevier, 2024)
Objectives: This study aimed to compare the effect of four decontamination methods on the level of residual contaminants in the re-usage of dental healing abutments. Materials and methods: In this experimental study, 50 used healing abutments were divided into five groups of ten as follows: 1. Control group: healing abutments were submerged in the ultrasonic device then autoclaved at 121 °C for 15 min; 2. Hypochlorite group: Same procedure as the control group, but the healing abutments were additionally immersed in 3 % hypochlorite for 20 min; 3. Chlorhexidine group: Same procedure as the control group, but the healing abutments were additionally treated with 12 % chlorhexidine; 4. Air polishing group: Same procedure as the control group, but the healing abutments were subjected to air polishing; 5. Hydrogen peroxide group: Same procedure as the control group, but the healing abutments were additionally exposed to 3 % hydrogen peroxide. Then, all healing abutments were stained with a protein-specific stain, Phloxine B. Five photographs were taken of each healing abutment, with four capturing the body (shank)and one capturing the top. All images were analysed, to measure the stained (contaminated) areas of each sample. The obtained data were analysed using statistical software (significance set at p < 0.05). Results: The one-way ANOVA test indicated that the average percentage of contamination residues on the occlusal surface did not show a significant difference among the five groups: control: 5.5 ± 2.8, sodium hypochlorite: 4.9 ± 2.5, Chlorhexidine: 5.3 ± 2.5, air polisher: 3.1 ± 1.8 and Hydrogen peroxide: 4.8 ± 3.1. (p = 0.26). The average percentage of residual contamination on the body surfaces (shank part) was significantly lower in the air polisher (1.7 ± 1.1) and sodium hypochlorite (2.4 ± 1.1) groups compared to the other three groups (Control: 6.1 ± 2.3, Hydrogen peroxide: 4.6 ± 0.7, Chlorhexidine: 5.4 ± 2.4) (p < 0.05). Conclusion: The results of this study showed that the use of sodium hypochlorite and air polishing, alongside autoclaving and ultrasonic cleaning, effectively reduced residual contamination on the body surfaces of healing abutments.